Self-differentiation and religious conversion process among the Malaysian Chinese Muslim converts - Loo, Tuck Yee (2020)
The balance between separateness and togetherness has become the primary concern to the knowledge area of self-differentiation and religious conversion. However, these two areas have not yet merged to study. The study explores the inter-influences between the two areas among the marginalized Malaysian Chinese Muslim converts. Research data were obtained through in-depth interviews. The researcher has conducted 19 interviews with five participants from the Northern region of Malaysia. The participants' selection criteria are Chinese Muslim converts who are above 25 years old with at least ten years of religious conversion experience. This study uses the Braun and Clarke Model as guidance in the data analysis process. Initial codes and themes were developed using the assistance of computer software. The researcher reorganized, refined and renamed the themes manually to form14 themes and 63 subthemes in answering the research questions. This study has divided the religious conversion process into five stages, which are the (1) initial attraction, (2) absorption, (3) adaptation, (4) assimilation and (5) integration. It shows that converts with different levels of self-differentiation might have different patterns of behaviours, thinking and emotions. In terms of the self-differentiation constructs among Chinese Muslim, some behaviours and responses might have different interpretation in the collectivistic, cultural and interpersonal context. The researcher develops the Unusual Life Experience Model (ULEM) based on Bowen Theory. The religious conversion process exposes converts to unusual life experience. It shifts the converts to the minority group, deviate them from compatriot norm, and associates them into new norms. The hardships and challenges in the unusual life experience facilitate the learning process and structural efforts to catalyze adulthood self-differentiation development. This study has added the religious conversion model, adulthood self-differentiation development process model, and human-God relationship into the body of knowledge. The researcher also provides suggestion to counsellors and future study.